2021
DOI: 10.1111/inm.12900
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Community Therapy – interventive strategies in the reduction of depression symptoms in adolescents: A quasi‐experimental study

Abstract: This study aimed to evaluate the effects of Integrative Community Therapy on depression symptoms in adolescents in the school context. This is a quantitative, quasi‐experimental, pre‐, and post‐test study that compared depression scores before and after the Integrative Community Therapy intervention was applied, conducted with 56 adolescent students. The guidelines recommended by the Standards for Quality Improvement Reporting Excellence were used to present this study. The instruments used for data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(36 reference statements)
0
4
0
1
Order By: Relevance
“…In the evaluation based on sex, ICT was effective for both sexes on the total SDQ score, but for the hyperactivity and relationship issues subscales, ICT was effective only for female adolescents. Other studies have also found differences in the effects of ICT based on sex in the assessment of anxiety (Alves, Felipe, Bressan, et al, 2021), and depression (Alves, Felipe, & da Moreira, 2021), with a significant reduction in symptoms for female adolescents only.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the evaluation based on sex, ICT was effective for both sexes on the total SDQ score, but for the hyperactivity and relationship issues subscales, ICT was effective only for female adolescents. Other studies have also found differences in the effects of ICT based on sex in the assessment of anxiety (Alves, Felipe, Bressan, et al, 2021), and depression (Alves, Felipe, & da Moreira, 2021), with a significant reduction in symptoms for female adolescents only.…”
Section: Discussionmentioning
confidence: 91%
“…Studies evaluating the effects of ICT on the adolescent population are scarce, which highlights the need for further research on this intervention with this population. However, the literature has already reported the positive effects of ICT on adolescent mental health, such as a decrease in depression (Alves, Felipe, & da Moreira, 2021) and anxiety (Alves, Felipe, Bressan, et al, 2021). Other studies in different contexts and with populations have also evidenced the positive effects of ICT in reducing depression and anxiety in college students (Boaretto et al, 2020; De Brum & Teixeira, 2020) and in drug addicts (Lemes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both reviews all studies were published in Brazil, mostly within nursing, and relied on qualitative methodologies. One nursing study, however, employed a pre-post test design (no comparison group) and found that ICT was associated with a reduction of depression over a five-week period for girls [ 40 ]. Overall, more rigorous testing of ICT is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, a Terapia Comunitária Integrativa (TCI), uma intervenção psicossocial criada no Brasil pelo psiquiatra Adalberto Barreto (BARRETO, 2019), pode ser um importante recurso para melhoria da qualidade de vida (CARTONILHO DE SOUZA RAMOS; LÚCIA BASILIO CARNEIRO; NUNES AZEVEDO DE MELO, 2020;NUNES et al, 2015;SILVA FRANCO et al, 2020). Destaca-se que a TCI tem sido eficaz na promoção da saúde emocional dos adolescentes (ALVES et al, 2021;ALVES;FELIPE;MOREIRA, 2021;FELIPE et al, 2020), que é um dos determinantes para a qualidade de vida (OPAS, 2018). Além disso, a TCI permite a criação de um ambiente de apoio, fortalece o vínculo entre os participantes e a capacidade de adaptação aos diferentes conflitos e problemas, é uma estratégia interventiva realizada em grupos mediante cinco etapas definidas: acolhimento, escolha do tema, contextualização, problematização e encerramento (BARRETO, 2019).…”
Section: Introductionunclassified